Large structural variations in the haplotype‐resolved African cassava genome. (10th November 2021) - Mansfeld, Ben N.; Boyher, Adam; Berry, Jeffrey C.; Wilson, Mark; Ou, Shujun; Polydore, Seth; Michael, Todd P.; Fahlgren, Noah; Bart, Rebecca S.
Summary: Cassava ( Manihot esculenta Crantz, 2 n  = 36) is a global food security crop. It has a highly heterozygous genome, high genetic load, and genotype‐dependent asynchronous flowering. It is typically propagated by stem cuttings and any genetic variation between haplotypes, including large structural variations, is preserved by such clonal propagation. Traditional genome assembly approaches generate a collapsed haplotype representation of the genome. In highly heterozygous plants, this results in artifacts and an oversimplification of heterozygous regions. We used a combination of Pacific Biosciences (PacBio), Illumina, and Hi‐C to resolve each haplotype of the genome of a farmer‐preferred cassava line, TME7 (Oko‐iyawo). PacBio reads were assembled using the FALCON suite. Phase switch errors were corrected using FALCON‐Phase and Hi‐C read data. The ultralong‐range information from Hi‐C sequencing was also used for scaffolding. Comparison of the two phases revealed >5000 large haplotype‐specific structural variants affecting over 8 Mb, including insertions and deletions spanning thousands of base pairs. The potential of these variants to affect allele‐specific expression was further explored. RNA‐sequencing data from 11 different tissue types were mapped against the scaffolded haploid assembly and gene expression data are incorporated into our existing easy‐to‐use web‐based interface to facilitate use by the broader plant science community. These two assemblies provide an excellent means to study the effects of heterozygosity, haplotype‐specific structural variation, gene hemizygosity, and allele‐specific gene expression contributing to important agricultural traits and further our understanding of the genetics and domestication of cassava. Significance Statement: The cassava varieties grown by subsistence farmers in Africa largely differ from the partially inbred reference genome due to their highly heterozygous nature. We used multiple sequencing technologies to assemble and resolve both haplotypes in TME7, a farmer‐preferred cassava line, enabling us to study the considerable haplotypic structural variation in this line.